Electrical Building at Night (American Colortype Company)
Embellished with hanging gardens, electric cascades and fountains, gilded pylons and paved terraces, the Electrical Building at A Century of Progress, Chicago's 1933 World's Fair, is the last word in modern architectural phantasy.